Immune-metabolic receptor GPR84 surrogate and endogenous agonists, 6-OAU and lauric acid, alter Brucella abortus 544 infection in both in vitro and in vivo systems. (September 2021) - Reyes, Alisha Wehdnesday Bernardo; Kim, Heejin; Huy, Tran Xuan Ngoc; Vu, Son Hai; Nguyen, Trang Thi; Kang, Chang Keun; Min, Wongi; Lee, Hu Jang; Lee, John Hwa; Kim, Suk
Abstract: Brucella abortus, one of the most important members of the genus Brucella responsible for human disease, is an intracellular pathogen capable of avoiding or interfering components of the host immune responses that are critical for its virulence. GPR84, on the other hand, is a seven-transmembrane GPCR involved in the inflammatory response and its induced expression was associated with B. abortus infection of RAW264.7 cells. Here we examined the effects of the reported GPR84 surrogate and endogenous agonists, namely 6- n -octylaminouracil (6-OAU) and lauric acid (LU), respectively in the progression of B. abortus infection in a cell and mouse models. The in vitro studies revealed the LU had bactericidal effect against Brucella starting at 24 h post-incubation. Adhesion of Brucella to RAW264.7 cells was attenuated in both 6-OAU and LU treatments. Brucella uptake was observed to be inhibited in a dose and time-dependent manner in 6-OAU but only at the highest non-cytotoxic concentration in LU-treated cells. However, survival of Brucella within the cells was reduced only in LU-treated cells. We also investigated the possible inhibitory effects of the agonist in other Gram-negative bacterium, Salmonella Typhimurium and we found that both adhesion and uptake were inhibited in 6-OAU treatment and only the intracellular survival for LU treatment. Furthermore, 6-OAU treatment reduced ERK phosphorylation and MCP-1 secretion during Brucella infection as well as reduced MALT1 protein expression and ROS production in cells without infection. LU treatment attenuated ERK and JNK phosphorylation, MCP-1 secretion and NO accumulation but increased ROS production during infection, and similar pattern with MALT1 protein expression. The in vivo studies showed that both treatments via oral route augmented resistance to Brucella infection but more pronounced with 6-AOU as observed with reduced bacterial proliferation in spleens and livers. At 7 d post-treatment and 14 d post-infection, 6-OAU-treated mice displayed reduced IFN-γ serum level. At 7 d post-infection, high serum level of MCP-1 was observed in both treatments with the addition of TNF-α in LU group. IL-6 was increased in both treatments at 14 d post-infection with higher TNF-α, MCP-1 and IL-10 in LU group. Taken together, 6-OAU and LU are potential candidates representing pharmaceutical strategy against brucellosis and possibly other intracellular pathogens or inflammatory diseases. Highlights: 6-OAU inhibited adhesion and Brucella uptake in RAW264.7 cells. 6-OAU decreased ERK phosphorylation, and TNF and MCP-1 secretion in macrophages. LU inhibited growth, adhesion, uptake and intracellular survival of Brucella . LU reduced p-ERK/JNK, nitrite accumulation, and MCP-1 but increased ROS production. 6-OAU and LU are potential preventive and therapeutic against Brucella infection.